Model Skematik Disain Bangunan Bank Sampah di Depok Jawa Barat - Endang Wahyuningtyas; Lubena Lubena; Ina Indah Rahmadani (Departemen Teknik Sipil dan Lingkungan, IPB University, 2018)
Waste bank is an activity of non-governmental program to maintain an environment health by separating household waste into organic and non-organic category. Waste bank is managed using a system such as banking conducted by officers. For Depok city, Waste bank program have a positive impact in declining of waste volume. However, the bank's activities are currently still carried out in the activist’s houses, public services house, and the path of the residential. Infact, waste bank have potency to support Ciliwung ecotourism planning by Depok government. This study uses Kaizen Management and Planning Method for Architectural Design. The result of this research is a schematic design model of Waste Bank building by research of society’s needs for the better environment health.Key words: eco-friendly building, energy saving, green building, waste bank model